Dukungan Kemampuan Awal, Fasilitas Belajar Terhadap Komunikasi Matematik Dan Dampaknya Pada Hasil Belajar Matematika Siswa Kelas VIII SMP Negeri 12 Surakarta Tahun 2016/2017 - Darmastuti, Murni, Dra. Nining Setyaningsih, M.Si (2017)
This study aims to: (1) analyze and test support prior knowledge and learning facilities for learning outcomes math indirectly through communication of mathematics, (2) analyzing and testing the support prior knowledge and learning facility directly to the communication of mathematics, (3) analyze and test the mathematical communications support to the mathematics learning outcomes. The subjects of this study were all students of class VIII SMP Negeri 12 Surakarta, amounting to 234 students, while the sample is 69 students drawn by proportionate random sampling technique. The data collection was conducted by questionnaire, and documentation. Data analysis technique used is path analysis previously performed data analysis prerequisite test: Liliefors normality test, linearity test, test multicollinearity, heteroscedasticity test and autocorrelation test. Research results: (1) there is support prior knowledge, and learning the mathematics learning outcomes indirectly through mathematical communication large of 0.540. (2) there is support prior knowledge, and learning directly against mathematical communication large of 0.464. (3) there is a mathematical communications support to the learning outcomes of mathematics with a value of 0.4851.